Comparing Gamified and Traditional Approaches in Neuroanatomy Education: Effects on Academic Performance and Critical Thinking - Ayesha Haque, Ayesha Haque (Indus Journal of Bioscience Research, 2025)
Objective: To compare the academic scores and critical thinking disposition of undergraduate dental students taught through gamification and traditional methods. Study Design: A comparative prospective study. Place and Duration of Study: Department of Anatomy, HITEC-Institute of Medical Sciences, Dental College, Taxila, from September to November 2022. Methodology: Fifty-four first-year Bachelor of Dental Surgery (BDS) students were randomly assigned to a control group (Group A) and an experimental group (Group B). Group A participated in traditional small-group discussions following large group interactive sessions (LGISs), while Group B engaged in a gamified learning intervention ("Heads Up"). Each intervention consisted of eight sessions, with knowledge assessed through MCQs after each session and critical thinking disposition compared using the Yoon Critical Thinking Disposition Inventory (YCTDI) after the study. Post-intervention, the groups crossed over to validate results. Data were analyzed using SPSS version 27, with statistical significance set at p ≤ 0.05. Results: Participants in Group B demonstrated significantly higher academic scores in MCQ-based tests compared to Group A (p < 0.05). Critical thinking disposition, particularly in the self-confidence subdimension, was also significantly higher in Group B (4.08 ± 0.88) compared to Group A (3.55 ± 0.86). Conclusion: Gamification is an effective, low-cost, and engaging strategy for teaching neuroanatomy, enhancing academic performance and critical thinking disposition among dental students.